Growth and development of bull-calves of different genotypes of created Ukrainian Angus meat breed - Доротюк, Е. М.; Прудніков, В. Г.; Колісник, О. І. (Scientific Progress & Innovations, 2012)
The results of research of growth and development of bullcalves of different genotypes of created Ukrainian Angus meat breed are presented. It is set that bull-calves are capable to keep the high average daily increase of living mass at the level of a 1000 gramme and more at the slow accumulation of fat during great while. At the intensive growing the bull-calves of the new created Ukrainian Angus meat breed in all age-old periods substantially excelled analogues which are widely spread in Ukraine. At the age of 18 months they attained living mass of 570 kg, against 425 kg of those in control group.